Timaeus and Critias - Plato (Oxford world's classics, 2008)
Timaeus, one of Plato's acknowledged masterpieces, is an attempt to construct the universe and explain its contents by means of as few axioms as possible. The result is a brilliant, bizarre, and surreal cosmos - the product of the rational thinking of a creator god and his astral assistants, and of purely mechanistic causes based on the behaviour of the four elements. At times dazzlingly clear, at times intriguingly opaque, this was state-of-the-art science in the middle of the fourth century BC. The world is presented as a battlefield of forces that are unified only by the will of God, who had to do the best he could with recalcitrant building materials.